Rayleigh lidar temperature profiles between 15 - 60 km during OZITOS campaign in Río Gallegos (51° 55 S, 69° 14 W), Argentina - Salvador, Jacobo Omar (2011)
The determination of temperature measurements from the Rayleigh scattering is an important remote sensing technique for obtaining stratospheric profiles. This technique is applied to signals acquired by a Rayleigh lidar (Light Detection and Ranging). Currently the Observatorio Atmosférico de la Patagonia Austral (51° 55?S, 69° 14?W) in Río Gallegos, Argentina is part of the UVO3Patagonia project in collaboration with the laboratory of Ozone and UV Radiation in the city of Punta Arenas, Chile distant 200 km, for more information www.uvo3patagonia.com. In this paper we showed the technique to measure temperature profiles in the stratosphere between 15-60 km altitude. We compared the temperature profiles obtained of the second ozone sounding campaign called OZITOS (OZone profile aT RíO GallegOS) carried out in March 2011 in Río Gallegos with the temperature profile retrieved by the Rayleigh lidar using the line of 355 nm, in the same period. The results presented in this paper are validated through intercomparisons with measurements made by MLS instrument (Microwave Limb Sounder) onboard the NASA AURA satellite platform and NCEP data.